Navigating the patient experience in primary healthcare clinics in the eastern province of Saudi Arabia: a secondary analysis study - Alhuseini, Mishael; Aljabri, Duaa; Althumairi, Arwa; Al Saffer, Quds (Frontiers in Medicine, 2025)
BackgroundThe patient experience is a critical indicator of healthcare quality, particularly in primary healthcare centers (PHCCs). Understanding patients’ perceptions is essential for improving service delivery and achieving patient-centered care. Despite healthcare reforms in Saudi Arabia, research on patient experiences in PHCCs in the Eastern Province remains limited.ObjectiveThis study aims to analyze patient experience trends in PHCCs within the Eastern Health Cluster of Saudi Arabia, identifying factors influencing satisfaction levels.MethodsA secondary analysis was conducted using patient experience data from the Ministry of Health’s Press Ganey survey. Data from 81,211 completed surveys collected between 2022 and 2023 were analyzed. The survey assessed seven domains of patient experience, and statistical tests, including t-tests and one-way ANOVA, were used to examine variations by demographic factors.ResultsThe overall patient experience score was 85.4%, with the highest satisfaction in the registration process (88.6%) and the lowest in the “moving through” domain (79%). Elderly patients (>65 years) reported higher satisfaction compared to younger adults (18–34 years) (p < 0.05). Male patients expressed slightly greater satisfaction than females (p < 0.05). Satisfaction varied across health networks, with Network C receiving the highest scores (88.8%) and Network B the lowest (83.2%). Patient satisfaction improved from 2022 (84%) to 2023 (86.4%).ConclusionThe patient experience in PHCCs within the Eastern Health Cluster has improved over time, reflecting ongoing healthcare reforms. However, disparities exist across demographic groups and health networks. Addressing patients’ concerns about wait times and service flows is necessary to enhance satisfaction. Future research should explore qualitative aspects of the patient experience and assess interventions to improve healthcare accessibility and equity.